Segmenting customers according to online word-of-mouth about hotels - Moliner-Velázquez, Beatriz (Serv Bus, 2021)
There is a renewed interest in the study of online word-of-mouth behavior due to the increasing use of the Internet and the development of social networks. This paper focuses on the receiver perspective to analyze the unequal influence of the antecedents of online consumer searches. The main purpose is to detect the heterogeneity of the effect of different motivations (convenience, risks reduction and social reassurance) and the volume of comments on the willingness to check online reviews. Based on 393 guests of hotels, a mixture regression model indicates the existence of three internally consistent segments, which reveal the varying influence on consumer intentions to look at online comments.